Slope Remediation Techniques and Overview of Landslide Risk Management - Danish Kazmi; Sadaf Qasim; I.S.H Harahap; Syed Baharom; Mudassir Mehmood; Fahad Irfan Siddiqui; Muhammad Imran (Salehan Institute of Higher Education, 2017)
Slope failures are common in many parts of the world which occur due to manifold reasons and they result in huge losses to the respective locals. This study evaluates the initiatives that can enhance the safety of slope by considering the remedial measures to deal with the factors causing slope instability and discusses the application of risk management strategies to address the problems that can cause the slope to fail. The methods for the remediation of slope include modification in slope geometry, drainage, use of retaining structures and internal slope reinforcement. This study also discusses the risk management process which is a hierarchical procedure that includes assessment and control of risk through different techniques in order to manage the uncertainties associated with the slope. It has been observed that the implementation of risk management strategy aids in the proper identification of risk and its severity which dictates the selection of appropriate remedial measure for the rectification of slope. For reducing the number of landslides, this study suggests the use of risk based strategies to curtail the chances of slope failure.